Effect of Nano-magnesium Oxide on Glucose Concentration and Lipid Profile in Diabetic Laboratory Mice: Effect of nano-magnesium oxide on diabetic mouse - Noushin Naghsh,; Shaghayegh Kazemi, (Iranian Journal of Pharmaceutical Sciences, 2014)
https://doi.org/10.22034/IJPS.2014.15248 Nano-sized drugs have better distribution than their identical forms. Magnesium is the cofactor of various enzymes in lipid and glucose metabolism. In this study, the effect of nano-magnesium oxide (nano-MgO) on glucose concentration and lipid profile in diabetes induced mice was evaluated in 21 laboratory mice. Mice were randomly divided into three equal groups (control, treatment, and placebo). Diabetes was induced in treatment and placebo group by injection of 60 mg/kg streptozotocin while control group was injected by saline. Treatment group was injected by 2 mg/kg of nano-MgO every 48 hours until the day 45. Serum glucose was measured at 3, 46, and 48 days. Concentration of triglyceride (TG), cholesterol, high density lipoprotein (HDL) and low density lipoprotein (LDL) was measured at day 48. Treatment and placebo group had higher glucose level at day 3 but treatment group at days 46 and 48 had lower glucose levels than placebo group. Diabetic mice had higher levels of TG, cholesterol, LDL and lower levels of HDL than control group in their serum samples. Treatment with MgO ameliorated change in glucose, TG, HDL and LDL level in treated mice. Our study has showed that administration of nano-MgO decreased glucose concentration and ameliorated TG, HDL and LDL levels in diabetes induced mice.